Answer:
![(1)\ logy\ =\ -sint\ +\ c](https://tex.z-dn.net/?f=%281%29%5C%20logy%5C%20%3D%5C%20-sint%5C%20%2B%5C%20c)
![(2)\ log(y+\dfrac{1}{2})\ =\ t^2\ +\ c](https://tex.z-dn.net/?f=%282%29%5C%20log%28y%2B%5Cdfrac%7B1%7D%7B2%7D%29%5C%20%3D%5C%20t%5E2%5C%20%2B%5C%20c)
Step-by-step explanation:
1. Given differential equation is
![\dfrac{dy}{dt}+ycost = 0](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7Bdt%7D%2Bycost%20%3D%200)
![=>\ \dfrac{dy}{dt}\ =\ -ycost](https://tex.z-dn.net/?f=%3D%3E%5C%20%5Cdfrac%7Bdy%7D%7Bdt%7D%5C%20%3D%5C%20-ycost)
![=>\ \dfrac{dy}{y}\ =\ -cost dt](https://tex.z-dn.net/?f=%3D%3E%5C%20%5Cdfrac%7Bdy%7D%7By%7D%5C%20%3D%5C%20-cost%20dt)
On integrating both sides, we will have
![\int{\dfrac{dy}{y}}\ =\ \int{-cost\ dt}](https://tex.z-dn.net/?f=%5Cint%7B%5Cdfrac%7Bdy%7D%7By%7D%7D%5C%20%3D%5C%20%5Cint%7B-cost%5C%20dt%7D)
![=>\ logy\ =\ -sint\ +\ c](https://tex.z-dn.net/?f=%3D%3E%5C%20logy%5C%20%3D%5C%20-sint%5C%20%2B%5C%20c)
Hence, the solution of given differential equation can be given by
![logy\ =\ -sint\ +\ c.](https://tex.z-dn.net/?f=logy%5C%20%3D%5C%20-sint%5C%20%2B%5C%20c.)
2. Given differential equation,
![\dfrac{dy}{dt}\ -\ 2ty\ =\ t](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7Bdt%7D%5C%20-%5C%202ty%5C%20%3D%5C%20t)
![=>\ \dfrac{dy}{dt}\ =\ t\ +\ 2ty](https://tex.z-dn.net/?f=%3D%3E%5C%20%5Cdfrac%7Bdy%7D%7Bdt%7D%5C%20%3D%5C%20t%5C%20%2B%5C%202ty)
![=>\ \dfrac{dy}{dt}\ =\ 2t(y+\dfrac{1}{2})](https://tex.z-dn.net/?f=%3D%3E%5C%20%5Cdfrac%7Bdy%7D%7Bdt%7D%5C%20%3D%5C%202t%28y%2B%5Cdfrac%7B1%7D%7B2%7D%29)
![=>\ \dfrac{dy}{(y+\dfrac{1}{2})}\ =\ 2t dt](https://tex.z-dn.net/?f=%3D%3E%5C%20%5Cdfrac%7Bdy%7D%7B%28y%2B%5Cdfrac%7B1%7D%7B2%7D%29%7D%5C%20%3D%5C%202t%20dt)
On integrating both sides, we will have
![\int{\dfrac{dy}{(y+\dfrac{1}{2})}}\ =\ \int{2t dt}](https://tex.z-dn.net/?f=%5Cint%7B%5Cdfrac%7Bdy%7D%7B%28y%2B%5Cdfrac%7B1%7D%7B2%7D%29%7D%7D%5C%20%3D%5C%20%5Cint%7B2t%20dt%7D)
![=>\ log(y+\dfrac{1}{2})\ =\ 2.\dfrac{t^2}{2}\ + c](https://tex.z-dn.net/?f=%3D%3E%5C%20log%28y%2B%5Cdfrac%7B1%7D%7B2%7D%29%5C%20%3D%5C%202.%5Cdfrac%7Bt%5E2%7D%7B2%7D%5C%20%2B%20c)
![=>\ log(y+\dfrac{1}{2})\ =\ t^2\ +\ c](https://tex.z-dn.net/?f=%3D%3E%5C%20log%28y%2B%5Cdfrac%7B1%7D%7B2%7D%29%5C%20%3D%5C%20t%5E2%5C%20%2B%5C%20c)
Hence, the solution of given differential equation is
![log(y+\dfrac{1}{2})\ =\ t^2\ +\ c](https://tex.z-dn.net/?f=log%28y%2B%5Cdfrac%7B1%7D%7B2%7D%29%5C%20%3D%5C%20t%5E2%5C%20%2B%5C%20c)